2013
DOI: 10.5588/ijtld.13.0070
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis in HIV-infected patients in Spain: the impact of treatment for LTBI

Abstract: TLTBI is effective in preventing the development of TB in HIV-infected patients, particularly in those who were TST-positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 23 publications
3
22
1
Order By: Relevance
“…Similar positive effects have been shown in HIV‐infected persons . Several other studies have also shown that treating latent tuberculosis is effective …”
Section: Premise 1: Tuberculosis Is a Problem And The Progress Towardsupporting
confidence: 74%
“…Similar positive effects have been shown in HIV‐infected persons . Several other studies have also shown that treating latent tuberculosis is effective …”
Section: Premise 1: Tuberculosis Is a Problem And The Progress Towardsupporting
confidence: 74%
“…In 2014, 142 197 newly diagnosed HIV infections were reported in the WHO European region [4], and 21 000 were provided with TB preventive therapy [16]. In a prospective cohort study in Spain, one-third of the HIV-positive cases without a history of TB were screened for latent TB infection, and of the cases with a positive screening result, approximately half received treatment for latent TB infection [34]. A cohort study in Switzerland showed that 69% of the patients without a history of TB were screened for latent TB infection, and 37% of those who tested positive received a full course of preventive treatment [35].…”
Section: Discussionmentioning
confidence: 99%
“…In studies from the high burden setting of the South African mines, the risk of TB infection has been shown to double within the first year, with Mtb strains significantly more likely to be unique within 2 years of HIV-seroconversion than later on in the disease, suggesting that TB may more likely be precipitated by reactivation early in the course of HIV and that recent reinfection with subsequent rapid progression occurs in more advanced immunosuppression [73]. Studies from low prevalence settings (Spain and Switzerland) suggest that the rate of TB in HIV-infected persons who are TST positive but untreated reduces over time, with most of the excess cases of TB compared with TST negative occurring within the first 2 years of follow-up; in total, only 10–12% of this very high-risk group developed TB over a follow-up period of up to 5 years [74,75]. …”
Section: The Natural History Of Tuberculosismentioning
confidence: 99%